Intravascular Lithotripsy in Calcified Coronary Lesions: A Single-Center Experience in “Real-World” Patients - Mastrangelo, Angelo; Monizzi, Giovanni; Galli, Stefano; Grancini, Luca; Ferrari, Cristina; Olivares, Paolo; Chiesa, Mattia; Calligaris, Giuseppe; Fabbiocchi, Franco; Montorsi, Piero; Bartorelli, Antonio L. (Frontiers in Cardiovascular Medicine, 2022)
Objectives This study aims to describe the outcome of intravascular lithotripsy (IVL) when used with different indications and to assess the short- and long-term outcomes of IVL-facilitated percutaneous coronary intervention (PCI). Background Intravascular lithotripsy can improve the results of PCI of calcified coronary lesions with a low rate of periprocedural complications. Methods A total of 105 consecutive patients with 110 calcified lesions underwent IVL. A total of 87 de novo lesions were treated by IVL with the following indications: 25 before attempting other balloon-based devices (primary IVL), 51 after the failure of non-compliant balloon dilatation (secondary IVL), and 11 after stent implantation because of stent under expansion (bailout IVL). In 23 lesions, IVL was used for the treatment of in-stent restenosis (ISR). Effectiveness (angiographic success) and safety [major adverse cardiovascular events (MACEs) and IVL-related procedural complications] endpoints were assessed. Results Angiographic success was achieved in 84.6% of lesions. Early MACEs were periprocedural MI only, ranging from 6.7 to 20% depending on MI definition. The flow-limiting dissections rate was 2.7%. A total of five (4.5%) IVL balloons ruptured during treatment with subsequent vessel perforation in 1 case. MACEs at 12 months were 13.3%, with TLR occurring in 8 lesions (12% primary IVL, 0% secondary IVL, 0% bailout IVL, and 21.7% IVL for ISR, p = 0.002). Conclusion Treatment of calcified coronary lesions with IVL in a “real-world” setting can be performed with high success, low rate of procedural complications, and an acceptable MACEs rate. Target lesion failure may be more frequent when IVL is performed for the treatment of ISR due to calcium-mediated stent under expansion.